A Systematic Review and Meta‐Analysis of HIV/AIDS Prevalence Among Transgender Populations Worldwide - Ghobad Moradi; Marzieh Soheili; Pourya Bahrami; Elnaz Ezzati Amini; Roya Rashti; Arian Azadnia; Farima Zakaryaei; Maryam Soheili; Yousef Moradi (Health Science Reports)
ABSTRACT Background and Aims The study's goal was to assess the global prevalence of HIV/AIDS infection in transgender people and to provide light on regional variances. Methods A systematic search was conducted across multiple databases, including PubMed (Medline), Scopus, Web of Science, Embase, Ovid, and PsycINFO, from inception until September 2023. Studies were selected based on predefined inclusion and exclusion criteria, and quality was assessed using the Newcastle–Ottawa Scale (NOS). Heterogeneity was evaluated using Cochran's Q and I‐squared statistics. A meta‐analysis was performed using the random‐effects model in Stata 17.0 (StataCorp, Texas, USA). A total of 3125 articles were identified, of which 37 studies met the inclusion criteria and were included in the systematic review and meta‐analysis. Results The global prevalence of HIV/AIDS among transgender populations was 24% (CI: 12%–39%). Regional analysis revealed higher rates of HIV/AIDS among male‐to‐female (MTF) transgender individuals in Asia (30%, CI: 5%–54%) and Africa (35%, CI: 13%–57%) compared to other regions. In contrast, female‐to‐male (FTM) transgender individuals in Asia had a higher prevalence (23%, CI: 9%–31%) than those in the Americas (11%, CI: 3%–23%). Conclusion Given the high prevalence of HIV/AIDS in the TG community worldwide and the significant variance within communities, it is critical to execute a comprehensive set of interventions to successfully prevent HIV/AIDS in transgender people.